Compound words used in Stephenie Meyer’s Twilight - Ririn Dwi Cahyanti (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2016)
This study was aimed at describing the types, the function, and the meaning of the compound words used in Stephenie Meyer’s Twilight. A qualitative method with the content analysis was applied in this study. The object of this study was compound words. For the data collection, it was used the techniques such as data collection, data reduction, data display, and conclusion drawing. This study was validated by using triangulation. The findings showed that there are 253 compound words. Based on the type of compound words, there are 5 compound words categorized as open form, 65 compound words categorized as hyphenated form, and 183 compound words categorized as closed form. Based on the function of compound words, there are 173 compound nouns, 13 compound verbs, and 67 compound adjectives. Referring to the meaning of compound words found from the contextual meaning, there are 140 words of the exocentric compound and 113 words of the endocentric compound.